An Analysis of Connotative Meaning in Born To Die Album by Lana Del Rey - Enggie Kharmelita; Maria Ramasari; Ardayati Ardayati (Institut Nalanda, 2024)
This research aimed to determine the types of connotative meaning found in Lana Del Rey’s Born to Die album, and the reasons of connotative meaning found in positive and negative by using Feng et al theory. This research used descriptive qualitative design. The data for this research was collected by using three steps, there were downloading, listening, transcribing, and identifying by the songs. The data analysis for this research used triangulation method, namely data condensation, data display, drawing and verifying conclusion. The result of this research was found that there are 65 connotative meaning found in lyrics of 12 songs on Born to Die album by Lana Del Rey. Furthermore, from 65 connotative meaning consisted of 33 positive connotative meaning and 32 negative connotative meaning. Moreover, from 37 lexicon types of connotative meaning consisted of 17 positive lexicon and 20 negative lexicon. Finally, from 28 lexicon types of connotative meaning consisted of 16 positive predicate and 12 negative predicate types.